Analisis Hukum Islam terhadap Praktik Gadai Sawah di Jorong Tabek Pala Nagari Talang Kecamatan Gunung Talang Kabupaten Solok - Angel Sophia Intan; Johan Agustian; B.R.E. Yunanda; M. Rafqi Amin; Herianto Hasibuan; Deby Ramadani Putri; Achyar Riyanda Halim (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
In Indonesia, Islamic law contributes significantly to the formation of the national legal system and legislation. However, in Nagari Talang, particularly in Jorong Tabek Pala, the situation shows otherwise. One of the main issues related to Islamic law is the inconsistency between the practice of pawning (gadai) and the provisions of Islamic law. Therefore, the research problems addressed in this study are: (1) How is the practice of rice field pawning conducted in Jorong Tabek Pala, Nagari Talang, Solok Regency? (2) How is the Islamic legal analysis of the implementation of rice field pawning in Jorong Tabek Pala, Nagari Talang, Solok Regency? This research is qualitative and descriptive in nature. The data sources consist of the pawners (rahin) and the recipients (murtahin) of the pawning in Jorong Tabek Pala, Nagari Talang, Gunung Talang District. Data were collected through interviews. Data analysis was conducted using data reduction, data presentation, and data verification. The validity of the data was tested using three techniques: source triangulation, time triangulation, and method triangulation. The findings of this study are: (1) The pawning practice carried out by the community in Jorong Tabek Pala is conducted as follows: the party in need of money offers their rice field to someone who has money and is willing to lend it. After finding someone willing to lend money, they make an agreement, either verbally or in writing. (2) From the perspective of Islamic law, the pawning practice in Jorong Tabek Pala falls under the category of riba (usury).